Evidence for a Prehypertensive Water Dysregulation Affecting the Development of Hypertension: Results of Very Early Treatment of Vasopressin V1 and V2 Antagonism in Spontaneously Hypertensive Rats - Verzicco, Ignazio; Tedeschi, Stefano; Graiani, Gallia; Bongrani, Alice; Carnevali, Maria Luisa; Dancelli, Simona; Zappa, Jessica; Mattei, Silvia; Bovino, Achiropita; Cavazzini, Stefania; Rocco, Rossana; Calvi, Anna; et al. (Frontiers in Cardiovascular Medicine, 2022)
In addition to long-term regulation of blood pressure (BP), in the kidney resides the initial trigger for hypertension development due to an altered capacity to excrete sodium and water. Betaine is one of the major organic osmolytes, and its betaine/gamma-aminobutyric acid transporter (BGT-1) expression in the renal medulla relates to interstitial tonicity and urinary osmolality and volume. This study investigated altered water and sodium balance as well as changes in antidiuretic hormone (ADH) activity in female spontaneously hypertensive (SHR) and normotensive Wistar Kyoto (WKY) rats from their 3–5 weeks of age (prehypertensive phase) to SHR’s 28–30 weeks of age (established hypertension-organ damage). Young prehypertensive SHRs showed a reduced daily urine output, an elevated urine osmolarity, and higher immunostaining of tubule BGT-1, alpha-1-Na-K ATPase in the outer medulla vs. age-matched WKY. ADH circulating levels were not different between young prehypertensive SHR and WKY, but the urine aquaporin2 (AQP2)/creatinine ratio and labeling of AQP2 in the collecting duct were increased. At 28–30 weeks, hypertensive SHR with moderate renal failure did not show any difference in urinary osmolarity, urine AQP2/creatinine ratio, tubule BGT-1, and alpha-1-Na-K ATPase as compared with WKY. These results suggest an increased sensitivity to ADH in prehypertensive female SHR. On this basis, a second series of experiments were set to study the role of ADH V1 and V2 receptors in the development of hypertension, and a group of female prehypertensive SHRs were treated from the 25th to 49th day of age with either V1 (OPC21268) or V2 (OPC 41061) receptor antagonists to evaluate the BP time course. OPC 41061-treated SHRs had a delayed development of hypertension for 5 weeks without effect in OPC 21268-treated SHRs. In prehypertensive female SHR, an increased renal ADH sensitivity is crucial for the development of hypertension by favoring a positive water balance. Early treatment with selective V2 antagonism delays future hypertension development in young SHRs.